2022
DOI: 10.15388/omee.2022.13.74
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Export: Evidence from Lithuania

Abstract: In this paper I apply the gravity model to analyse structural changes of Lithuania’s export during the first pandemic year. Lithuania was selected as a case of a small open economy with relatively high numbers of Covid-19 cases, on one hand, and a rather small decrease of its GDP growth in 2020, on the other. The research aims to fill the gap in the current literature by investigating heterogeneity in the goods export in terms of both product groups and export destinations. I also analyse whether the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…They found that both the macro level economic activity of countries and international trade of countries were influenced by the Covid-19 health crisis. In Lithuania, Petrylė (2022) found that mixed effects of Covid-19 on the country's exports with negative influences of exports on certain countries and positive influences of exports on other countries. The results of the present study bring more light into the effects of Covid-19 on international trade, by completing the results of previous studies as presented above.…”
Section: Discussionmentioning
confidence: 99%
“…They found that both the macro level economic activity of countries and international trade of countries were influenced by the Covid-19 health crisis. In Lithuania, Petrylė (2022) found that mixed effects of Covid-19 on the country's exports with negative influences of exports on certain countries and positive influences of exports on other countries. The results of the present study bring more light into the effects of Covid-19 on international trade, by completing the results of previous studies as presented above.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings about the influence of the COVID-19 burden on international trade showed very diverse situations in different countries. For example, in Lithuania [27], COVID-19 had mixed effects on the country's exports; exports towards certain countries were negatively influenced by COVID-19, while the exports towards other countries were positively influenced by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Khorana et al [18] discussed how, during the COVID-19 pandemic outbreak, the GDPs of Commonwealth countries were impacted, then showed how the economic downturns of those countries had a further negative impact on their international trade, pointing out at the relationship between GDP and international trade during the pandemic. In a study analyzing the influence of the COVID-19 pandemic on Lithuanian exports, GDP was one of the main regressors considered [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of publications discuss the potential and recorded impact associated with the spread of the pandemic (Büchel et al 2020;Meier and Pinto 2020;Bonadio et al 2021;Espitia et al 2022;Hayakawa and Mukunoki 2021;Liu et al 2022;Seuring et al 2022;Smith and Fatorachian 2023;Yudha and Roche 2023). A common finding is that the pandemic has forced an unprecedented economic shock (Gorynia and Tr ąpczy ński 2022;Rostan and Rostan 2022;Jurado and Kuo 2023) and challenged the trade flows worldwide (Cao et al 2021;Barbero et al 2021;Petryl ė 2022;Davidescu et al 2022;Yudha and Roche 2023;Enns et al 2023). These issues require multidimensional responses (Karuppiah et al 2022;Chen et al 2023;Smith and Fatorachian 2023) and adaptation for international trade, including GVC-related trade.…”
Section: Introductionmentioning
confidence: 99%